FINANCIAL ANALYSIS OF PIG BREEDING IN I MADE SUKARATA’S FARM, PADANGSAMBIAN KAJA VILLAGE, DENPASAR REGENCY - I D. P. W., Gunawa; Mudita, I M.; Sukanata, I W. (Jurnal Peternakan Tropika; Vol 6 No 2 (2018): May - August 2018, 2018)
This study aims to analyze the level of profits derived from the pig breeding business owned by Mr. I Made Sukarata with the maintenance scale of 47 mains. This activity was held in Banjar Batuparas, Padangsambian Kaja Village, West Denpasar on 18 October to 04 November 2017. Method of data retrieval conducted in this activity that is observation, practice directly in field, and interview to farmer. The variables observed in this activity are business analysis including net income, R / C ratio (Revenue Cost Ratio), breakeven price, and breakeven point of production. Poultry breeding business in the farm of Mr. I Made Sukarata with the production scale of 47 mains requires an investment cost of Rp. 168.100.000. Operasinal costs incurred within 6 months of maintenance of Rp. 163.167.926. Poultry breeding business in the father farmer I Made Sukarata with the maintenance scale of 47 mains within 6 months to earn a profit of Rp. 85.832.074 with R / C ratio 1,5. This breeding business reaches breakeven point when the price of seedlings Rp. 206,824 or produce 147 seeds per period   Keyword: business analysis, pig, breeding.